A qualitative study assessing the feasibility of implementing a group cognitive–behavioural therapy-based intervention in Sierra Leone. (10th May 2018) - Waterman, Samantha; Cole, Charles L.; Greenberg, Neil; Rubin, G. James; Beck, Alison
Abstract : Mental health support in Sierra Leone is sparse, and qualitative research into the feasibility of implementing psychological interventions is equally underdeveloped. Following the 2014 Ebola virus disease outbreak, South London and Maudsley NHS Trust were commissioned to develop a psychological intervention that UK clinicians could train national staff with minimal psychological experience to deliver to their peers. Following the completion of the stepped care, group-based cognitive–behavioural therapy intervention, qualitative interviews were conducted with the national team to identify key barriers and enablers to implementation of and engagement with this intervention. This article describes the key themes that came out of those interviews, and discusses the implications of these findings for future clinical teams.